Profitabilitas and Corporate Governance Disclosure: an Indonesian Study - Dwi Novi Kusumawati (The Indonesian Journal of Accounting Research, 2013)
This research aims to test empirically the relationship between profitability and the level of corporate governance voluntary disclosure. There are two streams of research regarding the direction of relationship between those two variables, making it interesting to be tested statistically in the context of corporate governance disclosure. The GCG disclosure level is measured using 161 items recommended by GCG Codes which are developed by KNKCG (2001). Data are taken from annual reports 2002. The result shows that, after controlling the model by several variables usually used in the disclosure research, profitability are negatively correlated with GCG disclosure. In other words, companies tend to give more comprehensive GCG disclosure when facing a slowdown in profitability measurements. Therefore, market has to take cautious in considering the GCG disclosure given by public companies since it could be used by management to cover bad performance.